(untitled) (The Peerian Journal, 2024)
The article explores some theoretical issues of formation and foreign experience in the development of banking innovations, customer service by commercial banks in the context of the introduction of the digital economy. Also, the current state and further development of remote banking services in commercial banks in the context of the introduction of digitalization of banking services are considered. In addition, the authors outlined ideas, scientific proposals and recommendations for the development of banking innovations in the Republic of Uzbekistan.